Adult mosquito control and honey bee safety - Steinke, T. L., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2004)
This fact sheet describes how to effectively protect honey bees during mosquito adulticide applications.
CEPEP 11/04.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Honeybee; Mosquitoes -- Control; Pesticides -- Environmental aspects